CaO2 pretreatment enhances fecal pollution indicator removal during mesophilic anaerobic digestion of sewage sludge - Yuhang Wang; Wenhao Fang; Hua Li; Ru Wang; Xinxin Wang; Xiaomeng Wang; Lixiang Zhou; Guanyu Zheng (npj Clean Water)
Abstract Municipal sludge retains fecal pathogens that pose challenges in its treatment and utilization. Mesophilic anaerobic digestion (MAD) fails to achieve adequate pathogen reduction while demonstrating inconsistent methane. To address these, the feasibility of reducing fecal pollution indicators, including Escherichia coli (EC), human-specific Bacteroides HF183 (HF183), human adenovirus (HAdV), JC and BK polyomaviruses (JCPyV and BKPyV), and crAssphage by combining MAD with CaO2 pre-treatment was assessed. Both ·OH and ·O2 − were produced during CaO2 pre-treatment. ·OH mainly accounted for the removal of these indicators, while ·O2 − reduced their infectivity. In MAD process, CaO2 pre-treatment accelerated the decay of most indicators with the elevated ammonia nitrogen in digested sludge. Overall, CaO2 pre-treatment and the MAD process predominantly contributed to the reduction of HF183, JCPyV and HAdV and the reduction of crAssphage, EC, and BKPyV, respectively, and combining MAD with CaO2 pre-treatment is an effective approach for removing fecal indicators from sludge.